2017
DOI: 10.1016/j.ssmph.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The household food insecurity gradient and potential reductions in adverse population mental health outcomes in Canadian adults

Abstract: PurposeHousehold food insecurity is related to poor mental health. This study examines whether the level of household food insecurity is associated with a gradient in the risk of reporting six adverse mental health outcomes. This study further quantifies the mental health impact if severe food insecurity, the extreme of the risk continuum, were eliminated in Canada.MethodsUsing a pooled sample of the Canadian Community Health Survey (N = 302,683), we examined the relationship between level of food insecurity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 54 publications
(90 reference statements)
10
78
0
2
Order By: Relevance
“…1,2 In Canada, household food insecurity has been linked to myriad physical and mental health problems, [4][5][6][7][8] to poorer chronic disease management 9,10 and to heightened nutritional vulnerability among adults and children, 11 but its impact on infant nutrition is less clear. Because breastfeeding offers a secure, low-cost, optimal food supply for infants, Canadian health policy and public health programs promote it as a key strategy to protect vulnerable infants from food insecurity.…”
mentioning
confidence: 99%
“…1,2 In Canada, household food insecurity has been linked to myriad physical and mental health problems, [4][5][6][7][8] to poorer chronic disease management 9,10 and to heightened nutritional vulnerability among adults and children, 11 but its impact on infant nutrition is less clear. Because breastfeeding offers a secure, low-cost, optimal food supply for infants, Canadian health policy and public health programs promote it as a key strategy to protect vulnerable infants from food insecurity.…”
mentioning
confidence: 99%
“…Our study raises serious concerns about the federal government's continued focus on foodsubsidy initiatives to improve food access in the North. Given the important health implications of food insecurity, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] more effective initiatives are urgently needed to address north ern food insecurity.…”
Section: Resultsmentioning
confidence: 99%
“…6,[42][43][44] The scale measures food access problems that range in severity from worrying about running out of food to compromising on the quality of food purchased, to eating less or going a whole day without eating because there was not enough money to buy food. 1,5 Because a single affirmative response to the module rep resents an experience of marginal food insecurity associated with adverse health outcomes, 20,21,23,24 households with 1 or more affirmative responses were considered food insecure, and households with no affirmative response were considered food secure. Households that answered none of the items were coded as missing and excluded from the analysis (n = 62).…”
Section: Measure Of Household Food Insecuritymentioning
confidence: 99%
“…). Evidence from international studies shows that the experience of food insecurity is linked to poor self‐reported health status and negative physical and mental health outcomes (Jessiman‐Perreault and McIntyre , Stuff et al . , Vozoris and Tarasuk ).…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity refers to uncertainty about the acquisition of an adequate quantity and quality of food in socially acceptable ways (Dowler and O'Connor 2012, Himmelgreen et al 2000, Purdam et al 2015. Evidence from international studies shows that the experience of food insecurity is linked to poor self-reported health status and negative physical and mental health outcomes (Jessiman-Perreault and McIntyre 2017, Stuff et al 2004, Vozoris and Tarasuk 2003. In the UK there are no national measures of food insecurity, so researchers have had to rely on information from charity-run foodbanks (Garthwaite et al 2015, Loopstra et al 2015, 2018 alongside other related metrics such as hospital admissions for malnutrition (Taylor-Robinson et al 2013) which likely underestimate the problem.…”
Section: Introductionmentioning
confidence: 99%